2016
DOI: 10.1002/jsfa.8041
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hyaluronic acid addition on the properties of smoked homogenised sausages

Abstract: HA has a potential of being a perfect functional food additive for meat industry, although further research regarding processing conditions should be performed. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…However, according to Nussinovitch [68] delaying moisture transport by alginate coatings prevent shrinkage, microbial contamination, and change of color of meat and meat products. Cooking loss (∆ W cs ) shows meat’s ability to retain water and fat and it is an important indicator during evaluation of profitability of production process [69]. The results obtained in this study are presented in Figure 11.…”
Section: Resultsmentioning
confidence: 84%
“…However, according to Nussinovitch [68] delaying moisture transport by alginate coatings prevent shrinkage, microbial contamination, and change of color of meat and meat products. Cooking loss (∆ W cs ) shows meat’s ability to retain water and fat and it is an important indicator during evaluation of profitability of production process [69]. The results obtained in this study are presented in Figure 11.…”
Section: Resultsmentioning
confidence: 84%
“…Third, since Streptococcus species are known for their pathogenicity, the production approach through bacterial fermentation poses the risk of product contamination with secreted exotoxins by bacteria and prevents its use in food applications. The addressed challenges were tackled by the genetic engineering of bacterial strains of Bacillus subtilis , Lactobacillus lactis , or Corynebacterium glutamicum , and this resulted in the production of a food-grade HA polymer with Generally Recognized As Safe (GRAS) status as per FDA 2020 [ 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chon et al [ 15 ] explored the properties of kefir with HA addition and found that the addition of HA did not affect the physicochemical and organoleptic properties of kefir and that HA could be used as a health-improving agent, especially in skin-damage and muscle. HA has been used in other foods, for example, Zajac et al [ 6 ] reported improved rheology and water-binding properties in smoked homogenized sausages after adding HA. Tan et al [ 11 ] recently reviewed the use of HA as a nano-delivery vehicle for food bioactive compounds and reported that these carriers have been developed with an improved solubility, stability, and bioavailability of polyphenols, lipids, and vitamins.…”
Section: Introductionmentioning
confidence: 99%
“…In aqueous HA solution, the anionically charged carboxyl groups usually combine with metal ions such as Na + , then form the high-hydrophilic Sodium Hyaluronate (SH) [ 2 ]. Based on its good water-holding and rheological properties, HA improves the texture of yogurt [ 3 ], enhances the homogeneity of smoked sausages [ 4 ] and contributes to the stability of skimmed milk in combination with carrageenan [ 5 ]. Interestingly, Kweon et al used HA to produce an edible film for alleviating dry mouth [ 6 ].…”
Section: Introductionmentioning
confidence: 99%